2016
DOI: 10.1007/s11150-016-9347-8
|View full text |Cite
|
Sign up to set email alerts
|

Moral hazard in marriage: the use of domestic labor as an incentive device

Abstract: This paper argues that some women in developing countries use domestic labor as a tool to incentivize husbands. A theoretical model is derived based on the traditions of rural Malawi, where men often supplement farm income with wage labor. As wage labor is not observed by the wife, this creates moral hazard: husbands may not make enough effort to bring home wages. The model predicts that women overcome this by using domestic labor as an incentive device: they increase their domestic labor and reduce their leis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Second, at the household level, fertility control may be object of non-cooperative bargaining between the spouses, in particular, for contraceptive methods that only women perfectly observe (Ashraf, Field and Lee 2014;Doepke & Kindermann 2019). More generally, the role of asymmetric information within the household is not yet explored (Walther 2017). Third, if parents have preferences over the gender composition of their offspring, fertility is better modeled as a sequential and uncertain process, where household size is likely endogenous to the sex of the last born child (Hazan & Zoabi 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, at the household level, fertility control may be object of non-cooperative bargaining between the spouses, in particular, for contraceptive methods that only women perfectly observe (Ashraf, Field and Lee 2014;Doepke & Kindermann 2019). More generally, the role of asymmetric information within the household is not yet explored (Walther 2017). Third, if parents have preferences over the gender composition of their offspring, fertility is better modeled as a sequential and uncertain process, where household size is likely endogenous to the sex of the last born child (Hazan & Zoabi 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For promising approaches, see, among others,Cubeddu and Ríos-Rull (2003),Goussé, Jacquemet and Robin (2017),Greenwood, Guner, Kocharkov and Santos (2016),Guler, Guvenen and Violante (2012),Walther (2017),Wong (2016).…”
mentioning
confidence: 99%
“…At this point, we note that the absence of domestic non-agricultural labor, which is currently subsumed in leisure both in the model and the data, may explain these findings. Walther (2017) shows that virtually all domestic labor in Malawi is carried out by women. 13 This implies that, to a first approximation, we overestimate women's leisure and underestimate their domestic labor in the data, but measure men's labor and leisure fairly accurately.…”
Section: Estimation Results Of the Structural Modelmentioning
confidence: 99%
“…Land is largely passed on through inheritance, often at the time of marriage, and determined by descent, which can be matrilineal or patrilineal (Walther, 2018). The predominant crop grown is maize, and agricultural production involves the joint labor supply of husbands and wives (see Walther, 2017, for more information on labor supply). Individuals' primary assets, and thus determinants of outside options, are their landholdings and capacity for labor supply.…”
Section: Malawian Contextmentioning
confidence: 99%
“…The presence of moral hazard in marriage is attributable to the fact that marriage is a type of contract between husband and wife and there is an inherent lack of full information in marriage (Walther, 2017). For example, Friedberg and Stern (2014) found that couples do not have a perfect knowledge of each other, and this asymmetric information would lead to quite high divorce rates in the absence of care within a marriage.…”
Section: Theoretical Backgroundmentioning
confidence: 99%